A clinical study of primary cutaneous localized amyloidosis - Chapalamadugu, Sahithi; Rao, A. Vijaymohan (International Journal of Research in Dermatology, 2020)
Background: Amyloidosis refers to abnormal extracellular tissue deposition of one of the biochemically unrelated proteins that share certain characteristic staining properties such as apple green birefringence of congo red stained preparations under polarized light. Amyloid deposition may occur in many organs of the body (systemic amyloidosis) or may be restricted to one tissue site (localized amyloidosis). Methods: Observational study was conducted in the Department of Dermatology, Narayana Medical College and Hospital, Nellore. In this study of 70 patients a complete history and clinical data was taken including details of presenting complaints, age, site, duration, course of the disease was recorded. Special importance was given to the friction history using different scrubs, family history and photo exposure. Results: Out of 70 patients of cutaneous amyloidosis 55 patients (78.6%) were of macular amyloidosis. Male:female ratio was 1:2.3. Majority of the patients were housewives (42.8%) and 28.5% of agriculturists. Majority of the patients (40) with cutaneous amyloidosis had disease duration between 2-5 years. In 70 patients of cutaneous amyloidosis 64.3% were symptomatic. 92% patients give history of using scrub. 50% of patients had history of photo exposure. Positive family history was seen in 7 patients (10%) and most common site involved was extensor aspect of arm. Conclusions: From our study it can be concluded that cutaneous amyloidosis is more common among females, most patients are symptomatic, majority have history of using scrub and photo exposure and most common site involved is extensor aspect of arm.